Specifics of Integration Processes in the Former Soviet Union: The Case of the Eurasian Economic Union - OINAROVA, Assem; ALIMKULOV, Ramazan; TLEPINA, Sholpan (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505//jarle.v9 3(33).34, 2018)
In the present settings, the development of the world economy follows a key trend that consists in regional economic integration. It is quite predictable that the member states of the Eurasian Economic Union (EAEU) are promoting the project of economic integration aiming to secure certain positions in the developing new structure of the global economic system. This study aims to establish whether EAEU meets the criteria for an international organization of regional integration, as well as to consider whether the EAEU countries can successfully combine their membership with the membership in the World Trade Organization (WTO). The study was based on specific techniques and methods for the research of phenomena and processes. In a bid to reach the objectives of the study, the authors considered the scientific opinions, online data sources, as well as the analytical data available on the official websites of EAEU, WTO and the Eurasian Economic Commission. The importance of the study lies in the actionable advice on the improvement of integration that was provided based on the analysis of the regional economic integration processes within EAEU. The study concludes that the EAEU was established in accordance with the norms of international law and that the Union possesses every attribute of an international organization. In addition to that, as a result of examining EAEU’s ‘outer borders,’ the study revealed certain problems for the member states in trying to maintain their EAEU membership alongside with the membership in WTO.